Multiple Positive Solutions for Nonlinear Semipositone Fractional Differential Equations - Wen-Xue Zhou; Ji-Gen Peng; Yan-Dong Chu (Discrete Dynamics in Nature and Society)
We present some new multiplicity of positive solutions results for nonlinear semipositone fractional boundary value problem D0+αu(t)=p(t)f(t,u(t))-q(t),0<t<1,u(0)=u(1)=u'(1)=0, where 2<α≤3 is a real number and D0+α is the standard Riemann-Liouville differentiation. One example is also given to illustrate the main result.